Scientific method in Ptolemy's Harmonics - Barker, Andrew, 1943-2021 (Cambridge University Press, 2000)
This book examines Ptolemy's scientific procedures for investigating the structures underlying musical melody. By providing an analysis of Ptolemy's theoretical apparatus, his strategies for integrating theory with observation, and his instructions for the design and conduct of experiments, the book offers a new starting-point for studying ancient scientific method.